Assay of 1l-myo-inositol-1-phosphatase using a fluorometric method - Churchich, Jorge E.; Kwok, Francis (Analytical biochemistry, 1991)
1L-myo-Inositol-1-phosphatase, an enzyme purified from brain tissues, catalyzes the dephosphorylation of 1L-myo-inositol 1-phosphate. This enzyme has become the subject of intense research interest, since myo-inositol is needed for the resynthesis of phosphatidylinositol. We have developed a sensitive fluorometric assay for detecting the activity of 1L-myo-inositol-1-phosphatase. The assay is based on o-aminobenzoyl beta-glycerophosphate fluorescence, according to the following principles: (I) The fluorescence yield of o-aminobenzoyl beta-glycerophosphate is increased by 2.75-fold in the presence of saturating concentrations of bovine serum albumin. (II) o-Aminobenzoyl beta-glycerophosphate has the same fluorescence yield as o-aminobenzoyl glycerol, but the latter does not bind to bovine serum albumin. (III) Dephosphorylation of the substrate, catalyzed by the monophosphatase, makes less o-aminobenzoyl beta-glycerophosphate available for binding to bovine serum albumin, thereby producing a decrease in the fluorescence intensity.